The Contractual Interpretation of Tipping J - Barber, Matthew (Victoria University of Wellington Law Review, 2016)
In the Supreme Court decision of Vector Gas Ltd v Bay of Plenty Energy Ltd, Tipping J put forward an approach to contact interpretation that, while indebted to that of Lord Hoffmann, was expressed differently and promoted the use of evidence of prior negotiations. Despite not gaining the support of any of the other sitting judges, this approach was swiftly taken up in the lower courts and, until recently at least, seems to have been accepted as representing New Zealand law. This article attempts a comprehensive examination of Tipping J’s approach. It concludes that, while coherent in principle, the detail of the approach is flawed in a number of ways, especially the way in which evidence of subsequent conduct is assumed to work. The future of Tipping J’s approach is considered.